The adaptor protein TRAF3 is an immune checkpoint that inhibits myeloid-derived suppressor cell expansion - Zhu, Sining; Lalani, Almin I.; Jin, Juan; Sant’Angelo, Derek; Covey, Lori R.; Liu, Kebin; Young, Howard A.; Ostrand-Rosenberg, Suzanne; Xie, Ping (Frontiers in Immunology, 2023)
Myeloid-derived suppressor cells (MDSCs) are aberrantly expanded in cancer patients and under other pathological conditions. These cells orchestrate the immunosuppressive and inflammatory network to facilitate cancer metastasis and mediate patient resistance to therapies, and thus are recognized as a prime therapeutic target of human cancers. Here we report the identification of the adaptor protein TRAF3 as a novel immune checkpoint that critically restrains MDSC expansion. We found that myeloid cell-specific Traf3-deficient (M-Traf3-/-) mice exhibited MDSC hyperexpansion during chronic inflammation. Interestingly, MDSC hyperexpansion in M-Traf3-/- mice led to accelerated growth and metastasis of transplanted tumors associated with an altered phenotype of T cells and NK cells. Using mixed bone marrow chimeras, we demonstrated that TRAF3 inhibited MDSC expansion via both cell-intrinsic and cell-extrinsic mechanisms. Furthermore, we elucidated a GM-CSF-STAT3-TRAF3-PTP1B signaling axis in MDSCs and a novel TLR4-TRAF3-CCL22-CCR4-G-CSF axis acting in inflammatory macrophages and monocytes that coordinately control MDSC expansion during chronic inflammation. Taken together, our findings provide novel insights into the complex regulatory mechanisms of MDSC expansion and open up unique perspectives for the design of new therapeutic strategies that aim to target MDSCs in cancer patients.